Securing lifelong retirement income : global annuity markets and policy - Mitchell, Olivia S.; Piggott, John (John R.); Takayama, Noriyuki, 1946- (Oxford : Oxford University Press, 2011)
As it becomes increasingly important to evaluate the risks and opportunities presented by an aging population, this book discusses products that manage longevity risk, the structure and safety of these products, and how policy can stimulate and strengthen them, within both emerging and older economies.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Pension trusts -- Management; Financial risk management